Arborização urbana de Catalão (GO): caracterização e proposta para a requalificação do sistema viário - (:unkn) unknown (Universidade Federal de Goiás, 2011)
In this research, the main goal is to describe and understand the urban afforestation in the road space of Catalão (Go), specifically, a delimited and interesting space, which the main object is the tree. In this way, the research about afforestation in this profile for studies and analysis, and the works realized using this ideas could also allow another goal, that was to offer, according to the principles of the primitive nature in the place, and the intention to improve the ecodynamics in Catalão city, actions for the requalification of the afforestation in the road urban system. The theoretical discussion is done by the ecodynamic approach, using the specialized literature giving emphasis also to the perception of the landscape,using other ways, for better comprehension of the subject, like soil analysis, trees total inventory, questionnaires to obtain the population perceptions and opinion. Through approaches, like reviews literature, field and laboratory researches, searching to understand the problems that exist in the urban afforestation of monitoring road, like to check if the afforestation how is made today is according to the place ecodynamic, and presents a proposal for the problems that arose in this analysis of the afforestation. The afforestation can be improved by the observance of the laws that are legal and the ones that are academic and scientific, some are Federal and Constitucional, others are from the state and the municipality, and rules that are related to the ecosystems nature that still remaining in the space cut for this study and that allows to observe and conclude about the ecodynamic of this space in study.
Urban forestry Catalan (GO): characterization and proposal for the upgrading of the road system
Keywords: Arborização viária urbana; Percepção; Ecodinâmica; Paisagem; Catalão (GO); Urban road dafforestation; Perception; Ecodynamic; Landscape; Catalão (Go); Arborização viária urbana; Paisagem; Ecodinâmica; Percepção; Catalão (GO); CNPQ::CIENCIAS HUMANAS::GEOGRAFIA